Application of Statistical Design to Assess the Critical Process Parameters of Ethanol Injection Method for the Preparation of Liposomes (Dhaka University Journal of Pharmaceutical Sciences, 2019)
In the present study custom screening design was employed to observe the effect of four critical process parameters on particle size and polydispersity index of the liposomal formulation made by ethanol injection method. The four process parameters selected were lipid ratio, rate of injection, phase volume ratio and rotational speed of magnetic stirring. Eight different liposomal formulations were prepared using the design. The formulations were subjected to particle size analysis. The analysis was done at a significance level p